Experience and identities in re-construction (2020)
The objective of the current research seeks at understanding how affects the knowledge re-construction, the professional action and the reconstitution of the teaching identity, the changes that have taken place in the last decades, the educational policies, the legislation, institutional changes, agreements, and the personal and professional experiences of each teacher. Originality: among the four dimensions that the project addresses (teaching development, experience, interactions and inclusion into organizations), we selected the approach of experience, focusing on the joint of knowledge of practice and professional identity. The method: The narrative research has researchers from the universities of Minho-Pt, Évora-Pt and UFR / UFMT / Br. As strategy, we opted to constitute the research corpus with narratives from three teachers of children. One from Brazil and two from Portugal, with 20 to 30 years of teaching practice. The question is, what are the most significant learnings identified by teachers? How is experience constituted as professional development? What experiences with children do teachers report as the most significant? To conclude, research shows that interactions with children, professional peers, and communities are the main pillar for the (re) construction of professional identities.